Neospora caninum and Toxoplasma gondii in naturally infected synanthropic (Muridae) and wild (Cricetidae) rodents from Argentina - Bentancourt Rossoli, Judith Victoria (2024)
Neospora caninum and Toxoplasma gondii are coccidian parasites (Phylum Apicomplexa) with canids and felids serving as their definitive hosts, respectively. Numerous studies worldwide have reported natural infections by these parasites in rodents. However, there is limited information available regarding the presence of these protozoans in rodents in our country. The objective of the present study was to detect T. gondii and N. caninum infections in rodents captured on dairy cattle farms in the Humid Pampa of Argentina. A total of 356 rodents were captured, including 212 from the family Muridae and 144 from the family Cricetidae, on dairy farms in three localities in the southeast of Buenos Aires province. Histopathological, serological and molecular analysis were performed. No cysts of either parasite was found in histological sections of organs and muscles. However, using IFAT, 1.4% (5/356) of the animals were seropositive for N. caninum (3/193 Mus musculus; 1/58 Oxymycterus rufus; 1/41 Necromys spp.) and 9.6% (34/356) were seropositive for T. gondii (19/193 M. musculus; 9/58 O. rufus; 3/41 Necromys spp.; 2/29 Akodon azarae; 1/11 Oligoryzomys flavescens). Only one individual (M. musculus) was positive for antibodies against both parasites. DNA was extracted from the brains of these 41 rodents. Using conventional PCR, T. gondii was detected in 9 out of 41 (22%) samples (5 O. rufus, 2 Necromys spp., 1 A. azarae, and 1 M. musculus), while N. caninum was negative in all samples. These results suggest that rodents may not play a role in the life cycle of N. caninum in dairy farms, whereas they could potentially act as reservoirs for T. gondii. This study represents the first investigation of N. caninum and T. gondii in cricetid rodents from Argentina and adds to the existing knowledge on these parasites in murine rodents.